The biomechanics of the sarcomere, the origin of muscular force - Formicola, D. (EWF Scientific Magazine, 2019)
The cytoskeleton is the complex matrix of filamentous and glomerular proteins that make up the framework of the sarcomere. The cytoskeleton is not limited to exercising a structural function, it assists muscular contraction both passively, exploiting its elastic properties, and actively, manifesting sensitivity to the ionic currents of sarcoplasm. In this article, we will describe the functions that the intrinsic components of the cytoskeleton perform to support sarcomeral contraction, reporting the results of the latest updates in the specific field of experimental microbiology. All the elements that make up the sarcomere participate in the phenomenon of shortening. The lack of only one of these elements drastically reduces the production of force by the single contractile unit of the muscle, as has been verified both by means of simulations with bioinformatics systems, and through direct experiments. The effects of muscular elastic components on sports performance are well known among training methodology experts. However, in relation to the high demands of competitive results advanced by the current world of sport, coaches, athletic trainers, physical trainers and physiotherapists have to take into account the latest updates on how the cytoskeleton components influence the production of force, to plan more effective intervention protocols on the improvement of athletic and sporting performance.